Effects of Vision Therapy on Visual-Motor Integration in Filipino Children with Down Syndrome. - Sy, Mamiko Fenella P. (Optometry & Visual Performance, 2025)
Purpose: To explore the effect on visual-motor integration in Filipino children with Down syndrome after vision therapy. Methods: Thirty-two (32) children aged 5 to 8 years old with Down syndrome and without strabismus, who were capable of copying figures, were initially evaluated, correcting refractive error and assessing for visual-motor deficiency. The participants were then enrolled in a 16-session vision therapy program scheduled once per week in-clinic for one hour. Therapy activities were provided for home reinforcement to be done by the patient (with parent and/or caregiver as the therapist) for 20 minutes daily. Three tests were performed to evaluate visualmotor integration ability before and after therapy: the Beery Developmental Test of Visual Motor Integration, the Incomplete Man test, and the Wold Sentence Copy test. Parents, teachers, and caregivers were also given a vision-related quality-of-life survey before and after the therapy program to report both how they observed the patient and any changes noted. Results: All of the children who completed the vision therapy program of 16 sessions showed significant improvement on all three tests (p>0.0001) and had meaningful experiences that have positively affected their quality of life. Conclusions: The results demonstrate the effectiveness of vision therapy in the improvement of visual-motor integration skills in children with Down syndrome, as well as improved behavior, as reported by the children's teachers, guardians, and/or parents.